Ginger as a Non-Pharmacological Intervention for Dysmenorrhea: Systematic Literature Review - herdian putri; ayu rosita; nareswari diska nugraha; Mia Ashari; ellatyas rahmawati tejo putri (Faculty of Health Sciences , Dr. Soetomo University, 2026)
Background: Dysmenorrhea is a discomfort during menstruation that occurs due to increased prostaglandins. Dysmenorrhea can reduce individual productivity. Ginger has active compounds that can reduce prostaglandin synthesis. Objective: This study aims to summarize experimental research on the effect of ginger administration on dysmenorrhea. Method: This study used the PRISMA method. Literature searches used several databases (ScienceDirect, crossreff, Google Scholar, willey, pubmed) with inclusion criteria of Indonesian and English, published 2021-2025, experimental research, research subjects in adolescents, and open access journals. Results: A review of 5 eligible articles showed that ginger is more effective than placebo in reducing dysmenorrhea. The majority of articles were pre-experimental. Pain scale measurements used the NRS and VAS scales. Pain scale measurements were carried out before and after the intervention. Conclusion: Ginger has been proven effective in reducing dysmenorrhea. However, there are several shortcomings in.